2018
DOI: 10.1016/j.optcom.2017.10.083
|View full text |Cite
|
Sign up to set email alerts
|

Single photon emitters in boron nitride: More than a supplementary material

Abstract: Keywords: boron nitride, single photon sources, defect centres in wide gap materials, micro-luminescence in visible spectral range ABSTRACTWe present comprehensive optical studies of recently discovered single photon sources in boron nitride, which appear in form of narrow lines emitting centres. Here, we aim to compactly characterise their basic optical properties, including the demonstration of several novel findings, in order to inspire discussion about their origin and utility. Initial inspection reveals t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 39 publications
7
37
1
Order By: Relevance
“…Such narrow ZPLs have been seen frequently in h-BN layers and were attributed to the presence of point-like defects, which confine electronic levels deep within the band gap and act as recombination centers, resulting in non-classical light emission 2,6 . For each location on the sample, we observe a unique pattern of PL peaks spanning across a large spectral band of~900 meV (Supplementary Note 2), in agreement with previous reports for h-BN flakes 6,7,11 , powder 12 and epitaxially grown films 24 . We then performed a more detailed study of the photophysical properties of the PL peaks from Fig.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Such narrow ZPLs have been seen frequently in h-BN layers and were attributed to the presence of point-like defects, which confine electronic levels deep within the band gap and act as recombination centers, resulting in non-classical light emission 2,6 . For each location on the sample, we observe a unique pattern of PL peaks spanning across a large spectral band of~900 meV (Supplementary Note 2), in agreement with previous reports for h-BN flakes 6,7,11 , powder 12 and epitaxially grown films 24 . We then performed a more detailed study of the photophysical properties of the PL peaks from Fig.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, these as well as other lines appearing in the emission spectrum at different energies have their own intrinsic direction of polarization axes. This suggests that the linear polarization of the PL signal most likely originates from the particular anisotropic structure of the emission center 8,12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this section, we review magneto-optical studies on SPEs in h-BN. Traditionally, non-magnetic SPEs involving singlet ground states, possibly intrinsic to a single defect or else from spin-coupled adjacent paired defects, have been associated as possible Group 2 emitters 37,112 . A recent study also reported no change in the optical spectra of h-BN defects with the application of a magnetic field 112 .…”
Section: Magnetic States For Quantum Device Applicationsmentioning
confidence: 99%